QUELLE CONCEPTION DE LA RENORMALISATION DANS LE MÉTIER D’ENSEIGNANT ? - Marcos Maldonado; Pascal Simonet; Célia Kohler (Questions Vives)
This article explores the tensions between prescribed norms and teachers’ real activity through the analysis of a training program designed to support their adoption of the Narramus method, recently introduced in Geneva’s primary schools. By leveraging activity analysis through simple and collective self-confrontations within a collaborative inquiry framework, the study examines how these approaches foster renormalization processes and contribute to the development of an occupational power to act. The analysis of discursive interactions highlights the dynamics of meaning negotiation and the role of trainers in these transformations. The study also questions the limitations of current training programs focused exclusively on teacher collectives, emphasizing the need to involve institutional prescribers in the renormalization process. This integration could transform real working situations by enhancing occupational power to act and expanding organizational leeway.